Analisis Penerapan Sistem Informasi Akuntansi Dalam Meningkatkan Kualitas Laporan Keuangan Pemerintah Daerah - Marpaida Situmeang; Ratna Sari Dewi; Rizqy Fadhlina Putri; Junita Putri Rajana Harahap (JURNAL AKUNTANSI AUDIT DAN PERPAJAKAN INDONESIA (JAAPI), 2025)
The Serdang Bedagai Regency Government has implemented PP 71 of 2010 concerning government accounting standards regarding the presentation of accrual-based financial reports. The purpose of the study was to determine the Analysis of the Implementation of Accounting Information Systems in Improving the Quality of Regional Government Financial Reports (Case Study at the Tebing Syahbandar District Office, Serdang Bedagai Regency). This study uses a qualitative research method, where researchers will collect data by observation, collect data in the field, and conduct direct interviews by directly visiting sources at the research location, interviews were conducted with the finance department. To obtain the data needed in this study, the author conducted this research at the Tebing Syahbandar District Office. Researchers can adjust the data collection techniques used to the conditions at the research location. Overall, the 2023 equity change report reflects improvements in the office's financial position and the effectiveness of financial management. The implementation of the Accounting Information System has helped achieve better transparency and supported positive equity increases, providing a strong foundation for future financial stability and growth. The use of the Regional Management Information System (SIMDA) in accrual-based regional financial management has brought about a significant transformation in the way local governments manage, record, and report their finances. SIMDA helps improve the accuracy, transparency, and speed of the financial report preparation process at the Tebing Syahbandar Sub-district Office.